Factors Influencing Satisfaction Of Online Learning Environment Among Malaysians - Chong, Boon Keng (2022)
The online learning has become a new normal for most learners in Malaysia, and learners are now gradually adapting to such learning environment owing to its flexibility, convenience and accessibility. The arrival of global pandemic COVID19 has pushed many educational institutions and organizations to adopt online learning approach in order to continue its operation. With that, satisfaction of online learners is critical to ensure learners achieve academic success and intention to continue study. Therefore, this research is essential for educational institutions, individuals, and government to determine and develop the best solutions to enhance satisfaction of online learning environment among learners in Malaysia. The aim of this research project is to examine the factors that influence satisfaction of online learning environment among Malaysians. The independent variables of this research include perceived usefulness, course quality, system quality, and instructor, whereas the dependent variable is satisfaction of online learning environment. A total of 280 sets of valid responses have been collected from the targeted respondents via Google Form which consist of three major sections. The collected data were analysed by using Statistical Package for the Social Sciences (SPSS) software Version 26 in order to further analyse and contribute to the findings and conclusion of this research topic. The findings have clearly showed that the factors of perceived usefulness, course quality, system quality, and instructor are significantly influence towards the satisfaction of online learning environment in Malaysia. The findings of this research found that system quality is most influential factor that influence satisfaction of online learning environment. However, there were no statistically significant difference in the satisfaction of online learning environment based on gender and age group. The implication and limitation of the study are also being further discussed and described. Recommendations are also being proposed in order to further assist future researchers in conducting similar research topic that related to satisfaction of online learning environment.